2010
DOI: 10.5194/acpd-10-20515-2010
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The vapor pressures and activities of dicarboxylic acids reconsidered: the impact of the physical state of the aerosol

Abstract: We present vapor pressure data of the C<sub>2</sub> to C<sub>5</sub> dicarboxylic acids deduced from measured evaporation rates of single levitated particles as both, aqueous droplets and solid crystals. The data of aqueous solution particles over a wide concentration range allow us to directly calculate activities of the dicarboxylic acids and comparison of these activities with parameterizations reported in the literature. The data of the pure liquid state acids, i.e. the dicar… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(37 citation statements)
references
References 58 publications
2
35
0
Order By: Relevance
“…[], and Soonsin et al . []. The range of K H values for MA and GA is compiled from the listed references.…”
Section: Resultsmentioning
confidence: 99%
“…[], and Soonsin et al . []. The range of K H values for MA and GA is compiled from the listed references.…”
Section: Resultsmentioning
confidence: 99%
“…At the same time, there is a discrepancy between the two EDB measurements of a factor of 7. It should be noted that the data reported by Soonsin et al (2010) are derived for particle evaporation at the later stages of particle evaporation (after the initial evaporation phase of several hours). The initial evaporation rate was significantly higher than that during the later stages.…”
Section: Discussion and Comparison With Previous Studiesmentioning
confidence: 96%
“…Several studies (Koponen et al 2007;Soonsin et al 2010;Zardini et al 2006) have shown evidence for the importance of the particle state for aerosol partitioning. Our assumption for laboratory-generated particles is that they are solid.…”
Section: Discussion and Comparison With Previous Studiesmentioning
confidence: 97%
See 1 more Smart Citation
“…To describe the partitioning of a compound to the aerosol, its liquid vapor pressure is required. Vapor pressures of polyacids have been measured since decades (Bradley and Cotson, 1953;Arshadi, 1974) but recently work in this area has intensified, with several publications in only this year (Booth et al, 2010(Booth et al, , 2011Frosch et al, 2010;Soonsin et al, 2010;Pope et al, 2010).…”
Section: Introductionmentioning
confidence: 99%